Thoracic electrical impedance tomography identifies heterogeneity in lungs associated with respiratory disease in cattle. A pilot study - Brabant, Olivia; Karpievitch, Yuliya V.; Gwatimba, Alphons; Ditcham, William; Ho, Ho Yin; Raisis, Anthea; Mosing, Martina (Frontiers in Veterinary Science, 2024)
Respiratory disease in cattle is a significant global concern, yet current diagnostic methods are limited, and there is a lack of crush-side tests for detecting active disease. To address this gap, we propose utilizing electrical impedance tomography (EIT), a non-invasive imaging technique that provides real-time visualization of lung ventilation dynamics.The study included adult cattle from farms in Western Australia. The cattle were restrained in a crush. A standardized respiratory scoring system, which combined visual, auscultation and clinical scores, was conducted by two non-conferring clinicians for each animal. The scores were blinded and averaged. During assessment, an EIT electrode belt was placed around the thorax. EIT recordings of ten suitable breaths were taken for analysis before the cattle were released back to the herd. Based on the combined examination scoring, the cattle were categorized as having healthy or diseased lungs. To allow visual interpretation of each breath and enable the creation of the quartile ventilation ratio (VQR), Flow/Tidal Impedance Variation curves (F/TIV) were generated for each breath. The analysis focused on two EIT variables: The novel VQR over time during inhalation and exhalation and global expiratory impedance (TIVEXP) adjusted by breath length. A mixed effects model was used to compare these variables between healthy and diseased cattle.Ten adult cattle of mixed ages were used in the current analysis. Five cattle were scored as healthy and five as diseased. There was a significant difference in the examination scores between the healthy and diseased group (P=0.03). A significant difference in VQR during inhalation (P=0.03) was observed between the healthy and diseased groups. No difference was seen in VQR over time during exhalation (P=0.3). The TIVEXP was not different between groups (P=0.36). In this study EIT was able to detect differences in inhalation mechanics when comparing healthy and diseased cattle as defined via clinical examination, highlighting the clinical utility of EIT.